Experimental Fatigue Life Estimation of AA5083 Aluminium Alloys Welded by Two Welding Processes- Gas Metal Arc (GMA) Welding and Friction Stir Welding (FSW) - Gori, Yatika; Verma, Rajesh P. (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*326.45px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.980112);" role="presentation">AA5083 aluminium alloys are widely used in automotive structure and naval structure due to its excellent <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*339.65px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.94659);" role="presentation">corrosion resistance and weldibility. All such applications require joining of aluminium alloys in most effective <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*352.97px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.955052);" role="presentation">and reliable method to withstand the <span dir="ltr" style="left: calc(var(–scale-factor)*229.13px); top: calc(var(–scale-factor)*352.97px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.967105);" role="presentation">fatigue failure. The main objective of the present work focuses on the <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*366.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.94482);" role="presentation">investigation of mechanical properties (tensile strength, percentage of elongation, weld hardness and fatigue <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*379.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.956021);" role="presentation">life) of AA5083 joint that are fabricated by two most popular welding proce<span dir="ltr" style="left: calc(var(–scale-factor)*383.83px); top: calc(var(–scale-factor)*379.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.786879);" role="presentation">sses- <span dir="ltr" style="left: calc(var(–scale-factor)*406.39px); top: calc(var(–scale-factor)*379.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.973824);" role="presentation">Friction Stir Welding <span dir="ltr" style="left: calc(var(–scale-factor)*496.18px); top: calc(var(–scale-factor)*379.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.948555);" role="presentation">(FSW) <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*392.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.86296);" role="presentation">and <span dir="ltr" style="left: calc(var(–scale-factor)*90.50px); top: calc(var(–scale-factor)*392.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.978324);" role="presentation">Gas Metal Arc <span dir="ltr" style="left: calc(var(–scale-factor)*156.38px); top: calc(var(–scale-factor)*392.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.982788);" role="presentation">(GMA) welding. The commercial plates of AA5083 aluminium alloys were used in the <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*405.77px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.989515);" role="presentation">study. The tensile properties and weld hardness were evaluated as per ASTMB-<span dir="ltr" style="left: calc(var(–scale-factor)*420.70px); top: calc(var(–scale-factor)*405.77px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.02031);" role="presentation">557M and ASTM E466 <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*419.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.899932);" role="presentation">standards. Fatigue test was <span dir="ltr" style="left: calc(var(–scale-factor)*185.09px); top: calc(var(–scale-factor)*419.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.937921);" role="presentation">performed at stress ratio 0.1 with 20Hz frequency. Both welding processes lead to <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*432.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.945965);" role="presentation">decrease of the material mechanical properties of the joint compared to parent metal. The FSW welding was <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*445.51px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.967692);" role="presentation">found more effective to achieve better tensile properties and fatigu<span dir="ltr" style="left: calc(var(–scale-factor)*354.55px); top: calc(var(–scale-factor)*445.51px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.983118);" role="presentation">e properties than GMA welding. Higher <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*458.71px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.89528);" role="presentation">fatigue scatter was ob<span dir="ltr" style="left: calc(var(–scale-factor)*158.90px); top: calc(var(–scale-factor)*458.71px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.919283);" role="presentation">tained in GMA welded specimens.